The aerodynamics of the wavy blade under the effect of fluctuated wind flow - Al-Bakri Basim A.R. (University of Belgrade - Faculty of Mechanical Engineering, Belgrade, 2021)
In the present study, the influence of the wavy edge blade on aerodynamic characteristics for the flow of blades at Reynolds number (Re) of 8×105 is numerically investigated based on the unsteady wind flow. Aerodynamic characteristics of a (sinusoidal leading edge) wavy NACA0015 aerofoil blade are carried out using ICEM 19.1 and ANSYS fluent. The numerical simulation is conducted then validated by experimental data with steady wind flow. This is conducted by employing the same Reynold's number in the experimental work. While, the unsteady flow was numerically performed at 1 Hz frequency of wind flow conditions. The main findings from this work show that the wavy blade can behave better in turbulent wind conditions with the maximum lift coefficient of 0.73 compared to 0.621 for the normal blade. However, the findings declare that the wavy blade stalled earlier than the normal one in the unsteady flow case. Similarly, it stalled at 12° angle of attack earlier than the normal one which was stalled at 14° in the steady flow case.